Tove Skutnabb-Kangas, Robert Phillipson, Ajit K. Mohanty and Minati Panda (eds.) 2009 - Lusekelo, Amani (AAeO - Afrikanistik-Aegyptologie-Online, 2011)
The present book offers evaluations of theories of multilingual education based on research in several contemporary issues of bilingual and multilingual school education throughout the world. Reading through it, one finds the answers to the questions on specific topics surrounding the plausible means of provisioning of effective and productive education in bilingual and multilingual societies in different countries. This is achieved, probably I should suggest, following the layout the book has.